MGMT-Positive vs MGMT-Negative Patients With Glioblastoma: Identification of Prognostic Factors and Resection Threshold. Issue 4 (12th January 2021) - Katsigiannis, Sotirios; Grau, Stefan; Krischek, Boris; Er, Kadir; Pintea, Bogdan; Goldbrunner, Roland; Stavrinou, Pantelis
Abstract: BACKGROUND: The importance of the O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation status as a predictive factor for the response to chemotherapy with temozolomide is well established. Its significance though at stratifying glioblastoma (GBM) patients in regard to their prognostic factors and the impact of surgical approach on them has not been identified. OBJECTIVE: To reveal possible differences in the prognostic factors and the impact of surgery between GBM patients stratified according to their MGMT status. METHODS: The authors retrospectively analyzed 186 patients with a newly diagnosed primary supratentorial GBM treated with surgical resection followed by standard radiation and chemotherapy. A prospective quantitative volumetric analysis of tumor characteristics identified on magnetic resonance imaging was performed. RESULTS: For the 109 patients with unmethylated MGMT promoter, extent of resection (EOR) represented independent predictor of survival, whereas residual tumor volume (RTV), Karnofsky Performance Score, and age were found to be independent prognostic factors of survival for the 77 patients with methylated MGMT promoter. For the group of patients with unmethylated and the group with methylated MGMT promoter, an EOR threshold of 70% and 98% and an RTV threshold of 1.5 and 1 cm 3 were identified, respectively. CONCLUSION: The selection of patients according to the MGMT promoter methylation status resulted in different prognostic factors and different resection thresholds for each patient population. A survival benefit seen from 70% EOR threshold in patients with MGMT unmethylated GBM supports the doctrine of maximum safe resection rather than the "all-or-nothing" approach.